B cells in systemic lupus erythematosus: Targets of new therapies and surveillance tools - Parodis, Ioannis; Gatto, Mariele; Sjöwall, Christopher (Frontiers in Medicine, 2022)
B cell hyperactivity is a hallmark of the complex autoimmune disease systemic lupus erythematosus (SLE), which has justified drug development focusing on B cell altering agents during the last decades, as well as the off-label use of B cell targeting biologics. About a decade ago, the anti-B cell activating factor (BAFF) belimumab was the first biological agent to be licenced for the treatment of adult patients with active yet non-renal and non-neuropsychiatric SLE, to later be expanded to include treatment of paediatric SLE and, recently, lupus nephritis. B cell depletion is recommended as an off-label option in refractory cases, with the anti-CD20 rituximab having been the most used B cell depleting agent to date while agents with a slightly different binding specificity to CD20 such as obinutuzumab have also shown promise, forming a part of the current pipeline. In addition, terminally differentiated B cells have also been the targets of experimental therapies, with the proteasome inhibitor bortezomib being one example. Apart from being promising drug targets, B and plasma cells have also shown promise in the surveillance of patients with SLE, especially for monitoring B cell depleting or B cell altering therapies. Inadequate B cell depletion may signify poor expected clinical response to rituximab, for example, while prominent reductions in certain B cell subsets may signify a protection against flare development in patients treated with belimumab. Towards an era with a richer therapeutic armamentarium in SLE, including to a large extent B cell altering treatments, the challenge that emerges is to determine diagnostic means for evidence-based therapeutic decision-making, that uses clinical information, serological markers, and gene expression patterns to guide individualised precision strategies.